Pharmacokinetic Interactions of Rolapitant With Cytochrome P450 3A Substrates in Healthy Subjects. (13th November 2018) - Wang, Xiaodong; Wang, Jing; Arora, Sujata; Hughes, Lorraine; Christensen, Jennifer; Lu, Sharon; Zhang, Zhi‐Yi
Abstract: Rolapitant (Varubi) is a neurokinin‐1 receptor antagonist approved for the prevention of chemotherapy‐induced nausea and vomiting. Rolapitant is primarily metabolized by the cytochrome P450 3A4 (CYP3A4) enzyme. Unlike other neurokinin‐1 receptor antagonists, rolapitant is neither an inhibitor nor an inducer of CYP3A4 in vitro. The objective of this analysis was to examine the pharmacokinetics of rolapitant in healthy subjects and assess drug‐drug interactions between rolapitant and midazolam (a CYP3A substrate), ketoconazole (a CYP3A inhibitor), or rifampin (a CYP3A4 inducer). Three phase 1, open‐label, drug‐drug interaction studies were conducted to examine the pharmacokinetic interactions of orally administered rolapitant with midazolam, rolapitant with ketoconazole, and rolapitant with rifampin. The pharmacokinetic profiles of midazolam and 1‐hydroxy midazolam metabolites were essentially unchanged when coadministered with rolapitant, indicating the lack of a clinically relevant inhibition or induction of CYP3A by rolapitant. Coadministration of ketoconazole with rolapitant had no effects on rolapitant maximum concentration and resulted in an approximately 20% increase in the area under the concentration‐time curve of rolapitant, suggesting that strong CYP3A inhibitors have minimal inhibitory effects on rolapitant exposure. Repeated administrations of rifampin appeared to reduce rolapitant exposure, resulting in a 33% decrease in maximum concentration and 87% decrease in area under the concentration‐time curve from time zero to infinity. Coadministration of rolapitant did not affect the exposure of midazolam. Rifampin coadministration resulted in lower concentrations of rolapitant, and ketoconazole coadministration had no or minimal effects on rolapitant exposure. Rolapitant was safe and well tolerated when coadministered with ketoconazole, rifampin, or midazolam. No new safety signals were reported compared with previous studies of rolapitant.